Determination of the median lethal concentration (LC50) of mycoinsecticides for the control of Ceratitis capitata (Diptera: Tephritidae) - QUEIROZ DE OLIVEIRA, FLÁVIA; DE LUNA BATISTA, JACINTO; MALAQUIAS, JOSÉ BRUNO; ALMEIDA, DALVA MARIA; DE OLIVEIRA, ROBÉRIO (Revista Colombiana de Entomología, 2010)
The aim of this study was to determine the median lethal concentration (LC50) of the commercial products Boveril WP®  (Beauveria bassiana) and Metarril WP® (Metarhizium anisopliae) on the larvae and pupae of the fruit fly, Ceratitis capitata. Insects used in this study came from a laboratory colony. The evaluated product concentrations were 10.00, 15.00, 20.00 and 25.00 g/L of water, which correspond, respectively, to 5.00x109, 7.50x109, 10.00x109 and 12.50x109   viable conidia/L of water for the two products, and in the control only water was applied. Third instar larvae and pupae of C. capitata were used in this study. Results showed an overall mortality of larvae with all conidial concentrations of M. anisopliae. The LC50   values for larvae were 2.99 and 2.97 g/L for Boveril®   and Metarril®, respectively, while for pupae they were 3.12 and 4.74 g/L for Boveril® and Metarril®, respectively. The high pathogenicity demonstrated by lower conidial concentrations of the tested products may mean greater efficiency from both economic and environmental points of view.